Prophylactic Treatment with VT-1161 Protects Immunosuppressed Mice from Rhizopus arrhizus var. arrhizus Infection - Gebremariam, Teclegiorgis (Antimicrob Agents Chemother, 2017)
We compared prophylactic or continuous therapy with the investigational drug VT-1161 to that with posaconazole in treating murine mucormycosis due to Rhizopus arrhizus var. arrhizus. In the prophylaxis studies, only VT-1161 resulted in improved survival and lowered tissue fungal burden of immunosuppressed infected mice. In the continuous therapy, VT-1161 outperformed posaconazole in prolonging mouse survival time despite its comparable effect in lowering tissue fungal burden. These results support the further development of VT-1161 against mucormycosis.